2016
DOI: 10.1093/mnras/stw035
|View full text |Cite
|
Sign up to set email alerts
|

The view of AGN-host alignment via reflection spectroscopy

Abstract: The fuelling of active galactic nuclei (AGN) -via material propagated through the galactic disc or via minor mergers -is expected to leave an imprint on the alignment of the sub-pc disc relative to the host galaxy's stellar disc. Determining the inclination of the inner disc usually relies on the launching angle of the jet; here instead we use the inclination derived from reflection fits to a sample of AGN. We determine the distorting effect of unmodeled Fe XXV/XXVI features and, via extensive simulations, det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 81 publications
2
19
1
Order By: Relevance
“…The inclination measured from the relativistic Fe line is very low (< 11°), which is consistent with the accretion disk being aligned with the face-on galaxy. While this is expected, we note that Middleton et al (2016) found that there is not a strong correlation between host and disk inclinations. We find only an upper limit on the spin, of < 0.25.…”
Section: Discussioncontrasting
confidence: 61%
“…The inclination measured from the relativistic Fe line is very low (< 11°), which is consistent with the accretion disk being aligned with the face-on galaxy. While this is expected, we note that Middleton et al (2016) found that there is not a strong correlation between host and disk inclinations. We find only an upper limit on the spin, of < 0.25.…”
Section: Discussioncontrasting
confidence: 61%
“…The iron abundance measured by the relxilllp model is consistent with the solar value, A Fe = 1.0 +0.3 −0.1 , which is also in agreement with the value of elemental abundances fixed in the refbhb model. We note that certain systematic uncertainties could be introduced when fitting the spectra with different reflection models (e.g., see the discussion in Middleton et al 2016), but the well agreement we find in i and A Fe determined by the refbhb and relxilllp reflection models indicates such uncertainties are probably minimal here.…”
Section: Power-law Dominant Statementioning
confidence: 62%
“…The broad iron line measured in other observations (Parker et al 2014a;Gallo et al 2015Gallo et al , 2019) also argues against a fully face-on configuration, as this would produce a relatively narrow line (although the inner disk does not necessarily have to be aligned with the larger AGN system, e.g. Middleton et al 2016). Similarly, we cannot distinguish between rotational broadening and velocity gradi-ents within the outflow itself, so the distance estimates from the velocity should be treated with caution.…”
Section: Componentmentioning
confidence: 82%